2002
DOI: 10.1177/07417136020523002
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Theory and Practice for Whole-Person Learning: Reconceptualizing Experience and the Role of Affect

Abstract: Although the importance of affect is acknowledged in the North American literature on adult learning and adult education, its role remains undertheorized. Ve argue that the inffluence of American pragmatism contributtes to a cultural bias favoring reflective discourse and, thus, theoretical inattention to the role of affect. IVe descr,ibe a theory of personhood developed by John Heron to explore howv his phenomenological lens on experience provides a more serviceable framewvorkJ in ivwich to understand the aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
86
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(86 citation statements)
references
References 7 publications
0
86
0
Order By: Relevance
“…This customization should be based on commonalities and differences among learners in considering how to incorporate appropriate experiences of embodiment. In previous studies, shared connections among learners was found to be highly important for fostering a sense of relatedness and comfort in approaching the body in learning (Freiler, 2007;Mills and Daniluk, 2002;Yorks and Kasl, 2002). The kinds of experiences provided also depend on the background and comfort level of the instructor or facilitator.…”
Section: Embodiment and Learning: Implications For Theory And Practicementioning
confidence: 96%
See 3 more Smart Citations
“…This customization should be based on commonalities and differences among learners in considering how to incorporate appropriate experiences of embodiment. In previous studies, shared connections among learners was found to be highly important for fostering a sense of relatedness and comfort in approaching the body in learning (Freiler, 2007;Mills and Daniluk, 2002;Yorks and Kasl, 2002). The kinds of experiences provided also depend on the background and comfort level of the instructor or facilitator.…”
Section: Embodiment and Learning: Implications For Theory And Practicementioning
confidence: 96%
“…Other experiential activities in higher education interrelate embodied learning with affect in social processes to analyze power differentials in society manifested in racism, sexism, and classism (Crowdes, 2000) and social representations of racial consciousness (Yorks and Kasl, 2002). Crowdes (2000) discusses experiential activities in an undergraduate sociology course using a progressive bowing exercise with prescribed conditions of authority and submission.…”
Section: The Nature Of Embodiment and Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…At the interpersonal and group level presentational, or expressive, knowing permits an empathic connection between individuals and is a pathway for critical discourse ; see Figure 5.1). This empathic connection is the basis for learningwithin-relationship amid diversity (Yorks and Kasl, 2002).…”
Section: How the Arts Assist The Collective Adult Learning Processmentioning
confidence: 99%